2022
DOI: 10.1002/bit.27993
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of the asparagine and glutamine dynamics in an industrial Chinese hamster ovary fed‐batch process

Abstract: Chinese hamster ovary (CHO) cell lines are grown in cultures with varying asparagine and glutamine concentrations, but further study is needed to characterize the interplay between these amino acids. By following 13 C-glucose, 13 C-glutamine, and 13 C-asparagine tracers using metabolic flux analysis (MFA), CHO cell metabolism was characterized in an industrially relevant fed-batch process under glutamine supplemented and low glutamine conditions during early and late exponential growth. For both conditions MFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…In low glutamine-containing medium, glycolytic fluxes were significantly increased while PPP was decreased 2-fold when compared to cultures growing in high glutamine medium. Pyruvate usage by the TCA cycle instead of lactate production was more important in low glutamine medium cultures, which was also observed by Kirsch et al [ 25 ]. An increase in TCA flux in such culture conditions was also reported in other studies, including in CHO-DHFR cells [ 50 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In low glutamine-containing medium, glycolytic fluxes were significantly increased while PPP was decreased 2-fold when compared to cultures growing in high glutamine medium. Pyruvate usage by the TCA cycle instead of lactate production was more important in low glutamine medium cultures, which was also observed by Kirsch et al [ 25 ]. An increase in TCA flux in such culture conditions was also reported in other studies, including in CHO-DHFR cells [ 50 ].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, another study concluded that glucose represents 65% of the entering carbon, with 10% coming from glutamine and 25% from other amino acids [ 23 ]. A lower contribution was also reported (40–50%) [ 24 , 25 ], although this can partly be explained by the fact that glucose consumption can vary simply due to different culture conditions, specifically, in the present case, culture volumes [ 26 ]. Besides these subtle differences, publications overall agree on the fact that glucose constitutes the main carbon source for growth.…”
Section: The Exponential Growth Phase: High Nutrient Uptake Enabling ...mentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies have associated glutamine depletion in cultures with the shift in lactate metabolism (Kirsch et al, 2021;Torres et al, 2018). Our data suggest that the decreased consumption of glutamine due to the interventions (observed in both cell lines) contributed to the delayed transition to lactate consumption in the CHO EPO-Fc cells.…”
Section: Assessment Of the Individual Effects Of Blimp1 Overexpression Low Temperature And Nabu On Cell Growth R-protein Expression And Msupporting
confidence: 52%
“…Glucose is the primary carbon source to the tricarboxylic acid (TCA) cycle, followed by glutamate and aspartate (non-protonatable amino acids as glutamine or asparagine, respectively) as secondary sources (Fig. 3a) 30 . We first interrogated the metabolic pattern of glucose upon uptake by senescent cells, as glucose is supposed to act as a principal contributor to the TCA cycle when cells enter senescence, a stage that is considered metabolically active 31 .…”
Section: Senescent Cells Exhibit a Distinct Profile Of Glucose Metabo...mentioning
confidence: 99%